Subjetividades juveniles y narrativas escolares en el Telebachillerato Comunitario en México - Salgado Escobar, Rocío Elizabeth (Universidad de Costa Rica, 2021)
In Mexico, the requirement for upper secondary education decreed in 2012 is still a pending task in rural and marginalized contexts where “Telebachilleratos comunitarios” are an expanding educational policy to incorporate young people previously excluded from the school system. The “Telebachillerato” has its origins in 1980, however, the school and community modality has only five generations and there is still little research from the perspective of its own actors. Therefore, the present study aimed to understand how the conditions of access to this type of education indicate the subjectivities of youth and their school experience.The qualitative-interpretative study was developed in the south of the state of Mexico, during the biennium November 2018-2020 under a dialogic-reflexive methodology deployed in a narrative workshop with a sixth semester group; the sessions were videotaped, transcribed and systematized in three analytical lines: conditions of access to schooling, youth subjectivities and participation in school. The results make visible school itineraries marked by the precarious implementation of a modality in which young people declare themselves the most despondent, but in which they also construct other modes of subjectivity through participation to demand better infrastructure, impact on school norms and pedagogical processes based on recognition. It is concluded that school subjectivities and narratives are founders of educational communities built on reflective dialogue and emerging youth meanings that are activated in the exercise of the right to education.